(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In the scientific scene, a lot of learning strategies and methods have emerged that help the learner in the learning process. Perhaps among these visual aids and mind maps is one of the most important means that contribute to stabilizing the information of the learner. Especially the game of volleyball, which consists of several basic skills, which through mastery we can obtain points directly on the opponent. In view of this, the importance of this research centered on making learning these skills an easy process by employing a learning method for the three mind map, which contributes to establishing conservation and facilitating the learning process, by observing the researcher that it is a graduate of physical education and found that there is a weakness in the learning process in the basic skills of volleyball and attribute The reason for this is due to the different learning capabilities of female students in their reception of information. Therefore, the researcher decided to try a new tool that she uses in the learning process that helps all learners and their different abilities, as it is a visual method that depends on what the learners receive from information about skills. E through the map of the mind, which is called a tree, and try to try it; perhaps it will teach the learners the best learning of these skills. One of the aims of the research is to identify the effect of the tree map on learning basic skills in volleyball. As for the research hypotheses, it included the absence of statistically significant assumptions between the tribal and posttest tests of the two groups in the tree maps and the performance of learning some basic skills in volleyball. The researcher concluded that the use of the tree map by the teacher has a clear impact on the process of learning some basic skills of volleyball and increases motivation and excitement in learning among students.